STUDY OF HEMOGLOBIN LEVELS ON HEMOLYSIS SAMPLE - Noor Febryani; Ikke Nanda Amalia; Intan Dwi Anggraeni; Gilang Nugraha (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2019)
Hemolysis can significantly affect the reliability of test results and occur in the pre-analytical phase. The aim of this study is to reveals the correlation of hemoglobin levels on hemolysis sample. This experimental study was carried out using samples from thirty students of Medical Laboratory Technology study program of the Nahdlatul Ulama University of Surabaya. Blood samples were treated by hard shaken in 30 times in order to damage the middle part of the blood sample. Data on hemoglobin levels were collected and analyzed using the Pearson Correlation Test before and after treatment with significant value p < 0.05 indicating that there was a significant correlation. Hemoglobin concentrations were strongly positive for the hemolysis of the sample (p = 0.000). The conclusion is that sample hemolysis has a potency to be the confounding factor on the hemoglobin test.